High-pressure liquid chromatography (HPLC) pigment concentration data and flow-cytometry picophytoplankton abundance and fluorescence data from serial dilution experiments conducted with surface mixed-layer water in extquotesingleExperimental stations extquotesingle during TAN1702 - Andrés Gutiérrez-Rodríguez; Mikel Latasa; Karl Safi; Matt Pinkerton; Scott D Nodder (PANGAEA, 2023)
Here we present data of phytoplankton pigment and flow cytometry (FCM) data from initial (T0) and final (T24) samples obtained from serial dilution grazing experiments set up with surface mixed layer water from subantarctic waters across the Campbell Plateau region southeast of New Zealand. Experiments were incubated onboard of the RV Tangaroa using deck flow-through incubators simulating in situ light and temperature conditions.
In: Gutiérrez-Rodríguez, A et al. (2023): Phytoplankton taxon-specific growth and microzooplankton grazing rates in subantarctic HNLC waters on and off Campbell Plateau southeast of New Zealand during austral autumn [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958525